UNIVERSITY EDUCATION: EXTRACURRICULAR ACTIVITIES OF STUDENTS IN ACADEMIC SUBJECTS - V I Kazarenkov; Petr Prokop; T B Kazarenkova (Peoples' Friendship University of Russia (RUDN University), 2015)
The article is devoted to a topical problem of university education - the organization of extracurricular activities of students in academic subjects. The materials characterizing the organization of various forms of extracurricular activities in academic subjects and the cooperation of teachers and students in such activities are presented in the article. The forms and methods of joint activity are defined; the features of interaction between teachers and students in extracurricular activities are highlighted.